2002
DOI: 10.1210/endo.143.1.8585
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Enters the Cerebrospinal Fluid through the Pineal Recess

Abstract: The pineal recess (PR), a third ventricle (IIIV) evagination penetrating into the pineal gland, could constitute a site of melatonin passage to the cerebrospinal fluid (CSF) and explain the high concentrations of melatonin in this fluid. To test this hypothesis, we characterized melatonin distribution in the IIIV of sheep by CSF collection in the ventral part of IIIV (vIIIV) and in PR. At 30 microl/min collection rate, melatonin concentrations were much higher in PR than in vIIIV (19,934 +/- 6,388 vs. 178 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(51 citation statements)
references
References 21 publications
0
50
0
1
Order By: Relevance
“…Interestingly, Mel concentration is 20 times higher in the third ventricle CSF than in plasma 53. Tricoire et al 54. further showed that Mel is released into the pineal recess (a third ventricle evagination penetrating into the pineal gland) and is then distributed throughout the ventricular system to possibly reach the periventricular binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Mel concentration is 20 times higher in the third ventricle CSF than in plasma 53. Tricoire et al 54. further showed that Mel is released into the pineal recess (a third ventricle evagination penetrating into the pineal gland) and is then distributed throughout the ventricular system to possibly reach the periventricular binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…The hormone is transferred by CSF to the SCN, other hypothalamic regions, the hippocampus, and choroid plexuses, where there are high affinity MT1 receptors [56]. Lateral ventricle (LV) melatonin concentrations have been reported to be far lower than 3V melatonin concentrations; this observation has been used in part to argue that 3V melatonin is not coming from recirculation via the plasma and choroid plexuses but rather through direct secretion into the pineal recess [159,183]. Indeed, in sheep, brain melatonin concentration close to the third ventricle walls and aqueduct of Sylvius is double that of plasma [110], penetrating 8-10 mm into brain as the concentration gradually falls.…”
Section: The Need For Csf-brain Isf Exchangementioning
confidence: 99%
“…In addition to this role in daily rhythms, the melatonin signal is essential for the integration of seasonal photoperiodic changes in physiology [6], thereby determining the best time for reproduction and associated physiological and behavioural changes to occur [7].…”
Section: Introductionmentioning
confidence: 99%